2016
DOI: 10.1364/oe.24.001865
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low temperature silicon nitride photonic integration platform

Abstract: High-quality SiNx films with controllable low stress and low optical loss are deposited at ultra-low temperature (75 °C) using inductively coupled plasma chemical vapor deposition (ICP-CVD). Two kinds of integrated photonic structures have been demonstrated that exemplify its viability as a photonic integration platform. A microcavity consists of two distributed Bragg reflectors (DBR) formed by alternating a total of 49 layers of SiNx and SiO2 with a total thickness of about 11.5 μm is grown without any cracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The mean Q of the data set was 110,000 (corresponding to 2.8 dB/cm), and the standard deviation was 8,900. Sidewall roughness due to patterning with i-line lithography is likely the leading contribution to linear propagation losses, as lower losses have been observed in waveguides of similar material when patterned with electron beam lithography (0.8 dB/cm) [24] as well as within this process when resist reflow was employed (1.8 dB/cm), as discussed in Sec. 4.…”
Section: Fabrication and Passive Devicesmentioning
confidence: 92%
See 3 more Smart Citations
“…The mean Q of the data set was 110,000 (corresponding to 2.8 dB/cm), and the standard deviation was 8,900. Sidewall roughness due to patterning with i-line lithography is likely the leading contribution to linear propagation losses, as lower losses have been observed in waveguides of similar material when patterned with electron beam lithography (0.8 dB/cm) [24] as well as within this process when resist reflow was employed (1.8 dB/cm), as discussed in Sec. 4.…”
Section: Fabrication and Passive Devicesmentioning
confidence: 92%
“…While most Si photonics foundry processes to date utilize crystalline Si as a waveguiding layer, deposited amorphous materials offer several advantages such as low-propagation-loss amorphous silicon (a-Si) [25,26] as well as SiN waveguides [24,27], a wide variety of indices of refraction, lower loss and crosstalk in waveguide crossings [27], and 3D layering [27][28][29][30]. A schematic of the layers used in this process is shown in Fig.…”
Section: Fabrication and Passive Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, inductively coupled plasma chemical vapor deposition (ICP-CVD) technique has been developed to deposit SiN x film under ultra-low temperature [25][26][27]. In our previous work, we have reported that a high quality SiN x film with thickness up to 2 μm can be achieved in a single growth process under ultra-low temperature circumstance [27], which shows great potential for active passive hybrid photonic integration [28,29].…”
Section: Introductionmentioning
confidence: 99%